The Impact of Special Autonomy on Education and Health Outcomes - Rumere, Victor; Sugiyanto, Catur; Sulistyaningrum, Eny (Universitas Negeri Semarang, 2022)
The purpose of the study is to analyze the impact of implementing on special autonomy in Papua on education and health outcomes. The main data are sourced from the 2015 Intercensus Population Survey. Educational outcomes are measured by the highest primary education completed, while the health outcome measure is the level of complaints of sickness. The impact of special autonomy on educational outcomes is analyzed using ordered logistic regression, while the impact of special autonomy on health outcomes is analyzed using ordered logistic regression and instrumental variables. The results of this studycomprise two findings. First, the implementation of special autonomy in Papua has not had an impact on basic education in the province, because education spending made by the regional government in implementing special autonomy in Papua has not been able to compensate for the needs of school -age children in households. Second, the implementation of special autonomy in Papua has a direct and indirect impact on household health outcomes. This shows that the health expendi tures made by the Regional Government in implementing Special Autonomy, through increasing the coverage of communit y health centers throughout Papua, bring benefits that are felt by households in the province.